An Ayurvedic Management of Nasal Polyposis - Atara, Achyuta (Indian J Otolaryngol Head Neck Surg, 2018)
A nasal polyp is a prolapsed pedunculated part of the oedematous mucosa of the nose or paranasal sinuses. It is inflammatory in origin and not a neoplastic (Bhargava in A short book of E.N.T. diseases. 9th edn. Usha Publication, [1]). This present study was aimed to treat Nasal polyposis with the drug administration through nasal as well as oral route. Total 61 patients were registered in three groups. Simple random sampling (alternate) method was adopted for the selection of the patients and selected patients were divided into 3 groups. Patients of Nasya Group and Nasya + Oral group received Ayurvedic treatment where as Controlled Group patients were treated with allopathic medicine. Duration of treatment was kept 3 months for Nasya Group and Nasya + Oral group, while 21 days for Controlled Group. Follow up was kept for 2 months at interval of 15 days each. Though all three groups showed significant improvement in subjective symptoms; Nasya Group and Nasya + Oral group showed better result in grading of Polyp.